An experimental investigation of the capsule velocity, concentration rate and the spacing between the capsules for spherical capsule train flow in a horizontal circular pipe - Ulusarslan, D; Teke, I (ELSEVIER SCIENCE SA, 2005)
This is the first experimental study on capsule train flow conducted with spherical polypropylene capsules simulating spherical ice capsules in district cooling systems. This article explains experimental determination of the capsule velocity, capsule concentration rates (C-dyn and C-st.) and the spacing between capsules for the flow of spherical capsule train in a horizontal straight pipe with water. The capsules are fabricated from polypropylene with density close to that of ice. The inner diameter (I.D.) and the length of the Plexiglass pipes constituting the test section, are 0.1 m and 6 in respectively and the diameter of the capsule is 0.08 in. Depending on the bulk velocity (V-m), the capsule velocity (V-c) and the spacing between capsules (l(c)) within a concentration range (C-dyn.) of 5-30% for 2.5 x 10(4) < Re < 1.5 x 10(5) has been investigated. According to experimental results, the velocity ratio (R-v = V-c/V-m) has always a value very close to 1.0 at different bulk velocities and concentration ranges and the average value of R-v is found to be 1.05. Due to high capsule-pipe diameter ratio (k), the capsules move along the axis of the pipe where maximum velocity is realized. When the concentration is kept constant, the average spacing between individual capsules does not change despite the increase in the bulk velocity. The capsule velocity increases almost linearly with the increase of the bulk velocity. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: capsule train; pipeline; ice; cooling systems; velocity ratio; Engineering